2019
DOI: 10.3892/ol.2019.10064
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of morphological parameters of giant cell tumor of bone in the knee

Abstract: The aim of the present study was to characterize the morphological parameters of giant cell tumor of bone (GCTB) in the knee. The imaging data of 250 patients with GCTB in the knee were retrospectively reviewed, and the morphological parameters were analyzed. The study included 137 cases with GCTB in the distal femur and 113 cases with GCTB in the proximal tibia. The maximal longitudinal diameter of the tumor was 6.616±2.322 cm in the femur group and 5.738±2.278 cm in the tibia group (P=0.003). The maximal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The metaphyseal sleeve was introduced with a low rate of loosening, providing a direct cementless fixation option at the metaphysis [ 12 ] and thus, complying with the principles of conservation to preserve as much bone stock as possible [ 13 ]. Lin et al [ 14 ] reported that in patients with giant cell tumor of bone (GCTB) in the distal femur, 80% of the maximal longitudinal diameter measurements of tumors in the distal femur were 4.4–8.9 cm and 80% of the shortest distance from the articular surface values were within 0.01–0.75 cm. So, excessive bone would be removed for the reconstruction with the current tumor prosthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The metaphyseal sleeve was introduced with a low rate of loosening, providing a direct cementless fixation option at the metaphysis [ 12 ] and thus, complying with the principles of conservation to preserve as much bone stock as possible [ 13 ]. Lin et al [ 14 ] reported that in patients with giant cell tumor of bone (GCTB) in the distal femur, 80% of the maximal longitudinal diameter measurements of tumors in the distal femur were 4.4–8.9 cm and 80% of the shortest distance from the articular surface values were within 0.01–0.75 cm. So, excessive bone would be removed for the reconstruction with the current tumor prosthesis.…”
Section: Introductionmentioning
confidence: 99%